Identification of Patients With Locally Advanced Gastric Cancer Who May Benefit From Adjuvant Chemoradiotherapy After D2 dissection: A Propensity Score Matching Analysis - Wang, Shu-Bei; Qi, Wei-Xiang; Chen, Jia-Yi; Xu, Cheng; Cao, Wei-Guo; Cai, Rong; Cao, Lu; Cai, Gang (Frontiers in Oncology, 2021)
Background: One of the most controversial areas in gastrointestinal oncology is the benefit of postoperative chemoradiotherapy (CRT) over chemotherapy (CT) alone after D2 dissection of locally advanced gastric cancer (LAGC). We aimed to identify the LAGC patients who may benefit from adjuvant CRT. Methods: We analyzed retrospectively 188 patients receiving radical gastrectomy with D2 dissection for LAGC in our hospital. Patients were divided into two balanced groups by using propensity score matching: CRT group (n=94) received adjuvant CRT, and CT group received adjuvant CT alone. Results: At a median follow-up of 26.50 months, 188 patients developed 79 first recurrence events (36 in CRT group and 43 in CT group). Our results showed that adjuvant CRT significantly decreased the risk of developing local regional recurrence (LRR) when compared to CT alone (14.9% vs. 25.5%, P = 0.044), while the estimated 3-year disease-free survival (DFS) was comparable between the CRT and CT groups (66.0% vs. 60.6%, p=0.239). In the subgroup analysis, a significantly decreased LRR rate was also observed in LAGC patients with N1-3a stage after adjuvant CRT (p=0.046), but not for N3b. Para-aortic lymph nodes (station No. 16) were the most frequent sites of LRR. After receiving radiotherapy, recurrence of 16 a2 region and 16 b1 region were significantly deceased (p=0.026 and p=0.044, respectively). Patients who received irradiation more than 4 months after surgery showed an increased risk of LRR (p=0.022). Conclusions: This study showed that adjuvant CRT significantly reduced LRR after D2 dissection of LAGC. Early initiation of adjuvant RT with clinical target volume encompassing a2 and b1 regions of para-aortic lymph nodes is recommended for pN1-3a patients after D2 dissection.